Resounding events : adventures of an academic from the working class - Connolly, William E. (Fordham University Press, 2022)
"A story of the experiences and experiments of one academic theorist from the American working class who probes how events resound into memory and thinking; such resonances sometimes help us to forge new concepts adjusted to emergent situations. Connolly says memory consists of recollections, organized dispositions without recollection, and remains--all can be activated by events and feed into thought. In focusing on the strange efficacies of diverse events such as the coma of his father, the experience of McCarthyism, tensions between working class life and norms of the academy, anti-war protests, the resurgence of white evangelicalism, the growing disaffection of the white working class, his sister's experience with white workers shifting to Trump, the neoliberalization of the university, the rise of aspirational fascism, and the acceleration of the Anthropocene Connolly examines how events jolt and animate thinking. He reviews tactics to spur creative thinking. This book thus explores how engaged intellectuals can become worthy of the events they encounter"--